2007
DOI: 10.1103/physrevb.75.184416
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic anomalous Hall effect in ferromagnetic metals studied by the multi-d-orbital tight-binding model

Abstract: To elucidate the origin of anomalous Hall effect ͑AHE͒ in ferromagnetic transition metals, we study the intrinsic AHE based on a multiorbital ͑d xz , d yz ͒ tight-binding model. We find that a large anomalous velocity comes from the off-diagonal ͑interorbital͒ hopping. For this reason, the present model shows a large intrinsic anomalous Hall conductivity ͑AHC͒ which is compatible with typical experimental values in ferromagnets ͑10 2 -10 3 ⍀ −1 cm −1 ͒, without the necessity to assume a special band structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
180
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(193 citation statements)
references
References 54 publications
(175 reference statements)
12
180
1
Order By: Relevance
“…In the metallic state, the Fermi level µ is located in the upper (E + k ) or lower (E − k ) branch, and the relationship According to the linear-response theory, the intrinsic Hall conductivity is given by the summation of the Fermi surface term (I-term) and the Fermi sea term (II-term) [23]. In previous work, we have shown that the I-term is dominant in many metals [12,14,24]. Using the 3 × 3 Green functionĜ 0 k (ω) = (ω + µ −Ĥ 0 ) −1 , the I-term of the OHC at T = 0 is given by [8,12] …”
mentioning
confidence: 99%
“…In the metallic state, the Fermi level µ is located in the upper (E + k ) or lower (E − k ) branch, and the relationship According to the linear-response theory, the intrinsic Hall conductivity is given by the summation of the Fermi surface term (I-term) and the Fermi sea term (II-term) [23]. In previous work, we have shown that the I-term is dominant in many metals [12,14,24]. Using the 3 × 3 Green functionĜ 0 k (ω) = (ω + µ −Ĥ 0 ) −1 , the I-term of the OHC at T = 0 is given by [8,12] …”
mentioning
confidence: 99%
“…′ sin k x sin k y , which breaks the mirror symmetry with respect to k x -and k y -axes, causes the large anomalous velocity [6]. This is the origin of huge SHE.…”
Section: Introductionmentioning
confidence: 99%
“…′ sin k y cos k x is called the "anomalous velocity", which is the origin of the Hall effects [3,6]. Since v a x has the same symmetry as k y , v a x v y can remain finite after the k-summations.…”
Section: Introductionmentioning
confidence: 99%
“…The interorbital terms are ξ 1 = −2t cos k x , ξ 2 = −2t cos k y , and Fig. 2 (a)), which breaks the mirror symmetry with respect to k xand k y -axes, causes the large anomalous velocity [8]. This is the origin of intrinsic Hall effects.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena are fundamental issues in recent condensed matter physics. [7,8]. In this article, we explain that the atomic orbital degrees of freedom causes the huge SHE and OHE in d-and f -electron systems.…”
Section: Introductionmentioning
confidence: 99%